Evolution and future prospects of adipose-derived immunomodulatory cell therapeutics. (February 2013) - McIntosh, Kevin R; Frazier, Trivia; Rowan, Brian G; Gimble, Jeffrey M
Over the past two decades, tissue engineering and regenerative medicine have evolved from what many considered a theoretical science to what is now a clinical reality. Tissue engineering combines biomaterial scaffolds, growth factors and stem or progenitor cells to repair damaged tissues. Adipose tissue, an abundant and easily accessed tissue, is a potential source of stromal/stem cells for regenerative therapeutic applications. Like bone marrow-derived mesenchymal stem cells, adipose-derived stromal/stem cells display both immunomodulatory and immunosuppressive properties. The adipose cells exert these actions, in part, through their secretion of paracrine growth factors. This review highlights recent developments in the isolation, characterization and preclinical application of adipose-derived cells and the challenges facing their translation into clinical practice.